Keujreun Blang’s Role in Strengthening Food Security and National Resilience - Nellis Mardhiah; Saputra, Jumadil; Zikri Muhammad; Cut Annisa Fitriati; Noka Omalia (Lembaga Ketahanan Nasional Republik Indonesia, 2025)
Purpose: This research is about how the development of local wisdom (especially Keujruen Blang) has been articulated into ACEH rice farmers’ socio-economic policy to build sustainable food security. The novelty of this study is that it relates the governance function of Keujruen Blang to Astagatra, endowed as national resilience, as a framing approach, which seems neglected in contemporary rural development literature. Study Design/Methodology/Approach: The study adopted a qualitative research design, utilising in-depth interviews, participatory observation, and document analysis to gather data from key stakeholders involved in rice farming and traditional governance. Findings: The results show that Keujruen Blang is not only a customary tool of conflict resolution and agricultural administration but also an important basis for social-cultural capital. The organisation maintains social order, controls group resources, and shows promise as an indigenous institution for locally sustainable policy development. By institutionalising its role within the policy of formal agriculture, the Astagatra in three dimensions (Trigatra) as well as another four pillars (Pancagatra), namely natural resources for Trigatra and law, social culture, economy, and political defence for Pancagatra. Originality/Value: The study confirms practical examples of the way in which local government can mainstream customary institutions into formal policy processes. It presents a participative, situationally sensitive, adaptive mode of governance that is applicable in other jurisdictions that strive for sustainable food security. In this respect, the research in this paper contributed to both academic discourses and policy interventions: it reveals how local cultural-based institutions can be effectively used to strengthen national resilience by integrating Astagatra.